Implementation of Raw Contract for Financing in Mandiri Syariah Bank - Enjang Sudarman (International Journal of Nusantara Islam, 2019)
This research is motivated by the existence of a standard contract which is a written agreement made or provided by one party, by including various contract clauses that have been standardized by one party without giving the other party the opportunity to negotiate them. The existence of a standard contract in the sharia business world is a pros and cons among the public, especially among legal experts, because in addition to making it easier and saving time, it is also considered to be against the principles of sharia, namely persecuting other parties. The theory used in this research is that the grand theory uses the rule of law theory; Middle Rangge Theory uses the Shahadah Theory from al-Syafi'i then the Social Juctice Theory; and the application theory uses a legal system supported by the theory of legal change. This study uses descriptive qualitative research, in collecting data, the authors use the method of observation, interviews and documentation using descriptive analysis to describe and describe the data obtained by using words or sentences that are separated according to the research data category in order to obtain a conclusion. The result of the research shows that the standard contract is legally valid because it has fulfilled the terms and conditions of contract in Islam which are marked by the signing of the standard contract by both parties as proof that both parties are equally pleased.